Psikoedukasi Pada Siswa SMPN 2 Dewantara Untuk Meningkatkan Motivasi Belajar Siswa - Safarina, Nur Afni; Astuti, Widi; Amalia, Ika; Munizar, Munizar; Mullah, Ikram (Edumedia Solution, 2023)
Learning motivation is a driving force that comes from outside and within the individual to foster enthusiasm in terms of learning. Motivation is very important for students which is used to foster student enthusiasm for learning, which can increase student learning motivation. Students in their learning process need encouragement to direct their learning behavior to achieve the desired achievement. Motivation encourages students to be able to learn to achieve their learning goals and objectives so that students are able to generate motion or move themselves to do something in order to increase learning motivation. This service aims to provide psychoeducation to 30 students of SMPN 2 Dewantara. The results of this dedication show that psychoeducation is beneficial to the participants, of the 30 students who were given pretest questions, the results obtained were an average of 57.66 from these students, which from these results it can be concluded that psychoeducation has an impact on students regarding student learning motivation, students also understand the problem of learning motivation, efforts to increase learning motivation, and the role of motivation in learning.